ANALISIS EMPIRIS TINGKAT KEPUASAN MAHASISWA PADA KUALITAS PELAYANAN DAN FASILITAS MENGGUNAKAN WEIGHTED LEAST SQUARES - Nendra Mursetya Somasih Dwipa; Titis Sunanti (Journal of Fundamental Mathematics and Applications (JFMA), 2018)
The present article aims to study the level of students’ satisfaction of PGRI Yogyakarta University towards service and facilities quality. To try and understand the factors which influence student satisfaction as well as consequences of it, this study test a weighted least squares model of student satisfaction. This study investigate determinant and dominant factors of the students’ satisfaction and its characteristics. The data were collected through a questionnaire administered to 160 students of PGRI Yogyakarta University to investigate their perceptions of the universities services. A questionnaire containing 30 questions has been used for data collection. The data were analyzed using the descriptive technique and the weighted least squares analysis. The measurement of the service quality is an important element to provide better, more efficient and more effective services.  SPSS Software and Cronbach alpha index have been used for data analysis and reliability. The reliability factor should be improved first because it is dominant in determining the students’ satisfaction. Quality indicators constituting the reliability factor include classroom, library, laboratory, public area, and information system. The results show that, by percentage, 2 indicators are in the very good category, only 5 indicators are in the good category, 9 indicators are in the fairly good category, and 14 indicators are in the poor category. The results indicate that the universities service quality needs to be improving. The results of the analysis show that five determinant factors of the students’ satisfaction include tangibles, reliability, responsiveness, assurance, and empathy. By the priority scale, the reliability factor should be improved first because it is dominant in determining the students’ satisfactionThe present article aims to study the level of students’ satisfaction of PGRI Yogyakarta University towards service and facilities quality. To try and understand the factors which influence student satisfaction as well as consequences of it, this study test a weighted least squares model of student satisfaction. This study investigate determinant and dominant factors of the students’ satisfaction and its characteristics. The data were collected through a questionnaire administered to 160 students of PGRI Yogyakarta University to investigate their perceptions of the universities services. A questionnaire containing 30 questions has been used for data collection. The data were analyzed using the descriptive technique and the weighted least squares analysis. The measurement of the service quality is an important element to provide better, more efficient and more effective services.  SPSS Software and Cronbach alpha index have been used for data analysis and reliability. The reliability factor should be improved first because it is dominant in determining the students’ satisfaction. Quality indicators constituting the reliability factor include classroom, library, laboratory, public area, and information system. The results show that, by percentage, 2 indicators are in the very good category, only 5 indicators are in the good category, 9 indicators are in the fairly good category, and 14 indicators are in the poor category. The results indicate that the universities service quality needs to be improving. The results of the analysis show that five determinant factors of the students’ satisfaction include tangibles, reliability, responsiveness, assurance, and empathy. By the priority scale, the reliability factor should be improved first because it is dominant in determining the students’ satisfaction.